2014
DOI: 10.3171/2014.7.jns131874
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a prognostic score for early mortality in severe head injury cases

Abstract: Object Traumatic brain injury (TBI) represents a large health and economic burden. Because of the inability of previous randomized controlled trials (RCTs) on TBI to demonstrate the expected benefit of reducing unfavorable outcomes, the IMPACT (International Mission on Prognosis and Analysis of Clinical Trials in TBI) and CRASH (Corticosteroid Randomisation After Significant Head Injury) studies provided new methods for performing prognostic studies of TBI. This study aimed to develop and externally validate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Furthermore, this information might be especially important in clinical trials for preventing enrolment of subjects for whom no benefit is expected from any type of intervention, which will help to maximize the chances of success [33]. Existing prognostic models including standard clinical risk factors, irrespective of the underlying pathophysiology, have proven limited utility to inform decision making [34][35][36], with only a few studies analyzing early death after a TBI [37,38]. The present work, consistent with previous research [36,39], provides evidence that blood-based biomarkers, rooted in the disease mechanisms, may yield independent and complementary prognostic information, and supports their integration into novel comprehensive multidimensional approaches for outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this information might be especially important in clinical trials for preventing enrolment of subjects for whom no benefit is expected from any type of intervention, which will help to maximize the chances of success [33]. Existing prognostic models including standard clinical risk factors, irrespective of the underlying pathophysiology, have proven limited utility to inform decision making [34][35][36], with only a few studies analyzing early death after a TBI [37,38]. The present work, consistent with previous research [36,39], provides evidence that blood-based biomarkers, rooted in the disease mechanisms, may yield independent and complementary prognostic information, and supports their integration into novel comprehensive multidimensional approaches for outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, TBI can be categorized into several classes such as mild, moderate and severe. These classifications are based upon criteria related to several indices, such as the Glasgow Coma Scale, length of post-traumatic amnesia, results of neuroimaging and whether or not the insult resulted from an open or closed skull injury (Gómez et al, 2014). Clinical cases of TBI in the civilian world are predominantly categorized as ‘mild’ and concussive in nature, requiring a visit to a hospital emergency department followed by discharge (Korley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that tSAH was an independent predictor of TBI mortality and severe neurological outcome2,10,21,28,31). Aminmansour et al described an association between tSAH and an increased incidence of cerebral vasospasm, with higher probability and greater severity in patients with severe TBI2).…”
Section: Discussionmentioning
confidence: 99%